Beyond art - Lopes, Dominic McIver (Oxford University Press, 2014)
The author articulates and defends a buck passing theory of art, namely that a work of art is nothing but a work in one of the arts. Having traced philosophical interest in theories of art to a reaction to certain puzzle cases of avant-garde art, he argues that none of the theories that have dominated philosophy since the 1960s adequately copes with these works. Whereas these theories have reached a dialectical impasse wherein they reiterate, and cannot resolve, disagreement over the puzzle cases, the buck passing theory illuminates the radical provocations of avant-garde art. In addition, when supplemented by a systematic framework for crafting theories of the individual arts, the buck passing theory grounds our empirical inquiries into the arts as well as our practices of appreciation and art criticism. Lopes seeks to model the diverse strategies employed by humanists and social and behavioural scientists who study the different arts. He gives the specificity of each art form a central role in our appreciative endeavours, and yet he stresses the continuity of the arts with similar, non-art activities such as fashion design, sports and games, cuisine, nature appreciation, and non-literary writing.